hnRNP E1 Regulates HPV16 Oncogene Expression and Inhibits Cervical Cancerization - Song, Li; Mao, Rui; Ding, Ling; Tian, Zhiqiang; Zhang, Mingxuan; Wang, Jiahao; Wang, Ming; Lyu, Yuanjing; Liu, Chunliang; Feng, Meijuan; Jia, Haixia; Wang, Jintao (Frontiers in Oncology, 2022)
hnRNP E1 (heterogeneous nuclear ribonucleoprotein E1) is an important RNA-binding proteins (RBPs) that plays a vital role in tumor development. Human papillomavirus 16 (HPV16) contains numerous sites that can bind to RNA/DNA and may be modified by multiple RBPs, which contribute to HPV gene expression and HPV-associated cancer development. However, the effects of hnRNP E1 on HPV16 oncogenes in the development of cervical lesions remain unclear. A total of 816 participants with different grades of cervical lesions were enrolled from a community-based cohort established in the Shanxi Province, China. The Gene Expression Omnibus (GEO) database was used to analyze hnRNP E1 mRNA expression in cervical lesions and its relationship with HPV. Cells with up_ and down-regulated hnRNP E1 were established. hnRNP E1 functions were evaluated using cell counting kit-8, flow cytometry analyses and chromatin immunoprecipitation sequencing. Our results showed that hnRNP E1 expression was linearly dependent on the severity of the cervical lesions. Low expression of HPV16 E2, high expression of E6, and a low ratio of E2 to E6 could increase the risk of cervical lesions. hnRNP E1 expression was correlated with HPV16 oncogene expression. hnRNP E1-relevant genes were involved in the dopaminergic synapses, Wnt signaling pathway, gnRH secretion, and mTOR signaling pathway. hnRNP E1 significantly inhibited cell proliferation, induced apoptosis, arrested the cell cycle at the G0/G1 stage, and decreased HPV16 E6 expression. Our results indicate that hnRNP E1 could downregulate HPV16 E6 oncogene expression and inhibit cervical cancerization, which sheds new light on preventing the carcinogenicity of HPV across a range of diseases by regulating RNA-binding proteins.